Synthesis and Characterizations of Chitosan/EDTA/PVA Nanofiber for Antimicrobial Applications - Ammar M. Hamza (Journal of Global Pharma Technology, 2016)
The aim behind this study was to fabricate thermally crosslinked Chitosan. (CS)/ Ethylenediaminetetraacetic acid (EDTA)/ Poly (vinyl alcohol) (PVA) and pure chitosan as nano fiber mats. The CS/EDTA/PVA nanofibers and/or pure chitosan were prepared using elctrospinning technique. The suitable cross linking ratio and cross linking times for CS/EDTA/PVA nanofiber were look into. The scanning electron microscopy and X-ray Diffraction was utilized to investigate influence of adding polymers to chitosan on the morphological and diameter of the nanofiber. The FTIR was carried out to evaluate the spectroscopic properties and functional groups which present in the compounds. The antimicrobioal test was examined by using Staphylococcus Aureus which is a spherical gram-positive bacterium and common test for antimicrobial applications. The result of antimicrobials test was made the CS/ESTA/PVA as nano fiber is viable materials for biomedical applications.Keywords: Antibacterial, Biopolymer, Nanostructure, Physical properties.